Nutrient availability and pH level affect germination traits and seedling development of Conyza canadensis - Caroline Maldaner Follmer; Ana Paula Hummes; Nadia Canali Lângaro; Claudia Petry; Diovane Freire Moterle; Edson Campanhola Bortoluzzi (Scientific Reports, 2021)
Abstract Reducing pesticide application in agricultural land is a major challenge for the twenty-first century. Responses of weed seed’s germination and seedling’s early development to chemical soil conditions around the seed may be a promising way to aid weed control in a no-till system. Thus, the objective of this work was to test, under controlled conditions, whether different chemical conditions affect the germination and development of horseweed [Conyza canadensis (L.) Cronquist]. We used, as treatment, solutions containing different nutrients (P, K, Ca, and Mg), separately and in combination, and at two pH levels (4.8 and 6.5). Phosphorus alone inhibited horseweed seed germination at ~ 7 times while had ~ 4 times reduction in final germination percentage and germination speed index for both pH tested. Other nutrients tested had a no-effect in germination speed index compared to the control treatment. Potassium alone or associated with other ions (P, Ca, and Mg) at pH 4.8 had a synergistic effect on seedling development (root and shoot length). In the same way, K associated with Mg was synergistic to the root length at pH 6.5. Seeds in the control treatment (distilled water) presented a high germination speed index at pH 6.5, while at low pH this parameter was higher when in association with KMg, PMg and Ca. The findings demonstrate that seed germination traits and seedling development of horseweed depend on nutrient kind exposure and pH conditions in the seed environment. This work suggests that adequate topsoil management (i.e., pH and nutrient availability) may aid to reduce weed germination, because, it consists of an important factor of weed occurrence in agricultural areas.